THE ROLE OF VIRTUAL MUSEUMS IN HISTORY EDUCATION - Temur Abdullayev (Western European Studies, 2024)
This article examines virtual museums and their importance in education, the educational quality of the virtual museum as an additional tool in teaching history, and how much it helps to increase the student's interest in science. The importance of virtual museums in the period of technological development is also discussed
Keywords: virtuаl museums; histоry educаtiоn; digitаl technоlоgies; culturаl heritаge